2015
DOI: 10.1037/lhb0000148
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathic traits as predictors of future criminality, intimate partner aggression, and substance use in young adult men.

Abstract: This study examined the prospective relation between Youth Psychopathic Traits Inventory (YPI) scores and various negative outcomes in a community sample of young men. Official criminal records and self-reported outcomes, including criminality, physical and relational aggression against intimate partners and excessive substance use, were obtained on average 5.4 years (records) and 3.5 years (self-reports) after the YPI assessment. Results showed that psychopathic traits measured with the YPI (approximately at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 61 publications
(131 reference statements)
1
38
1
1
Order By: Relevance
“…Perhaps, the fact of having the disposition to steal, in a given moment, or the planning of a theft/robbery, involves lying, deceiving, defrauding the trust of others, and probably also requires a degree of underestimation of the ability of the deceived ones to realize of the intentions of the scammers, or that when the deceived ones become able to realize of the intentions of the scammers, they (the scammers) will be already out of reach; apparently, these considerations might be operating both in the people of the general community prone to stealing, as well as in the group of prisoners, but to a greater degree in the latter group. Finally, owing to the contradictory nature of the reported findings about the importance of the affective and interpersonal dimensions of psychopathy as a risk factor to predict criminal behavior, it is probably better to wait for more research to be done about this matter before taking a decision in favor or against these empirical findings (Colins, Andershed, & Pardini, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps, the fact of having the disposition to steal, in a given moment, or the planning of a theft/robbery, involves lying, deceiving, defrauding the trust of others, and probably also requires a degree of underestimation of the ability of the deceived ones to realize of the intentions of the scammers, or that when the deceived ones become able to realize of the intentions of the scammers, they (the scammers) will be already out of reach; apparently, these considerations might be operating both in the people of the general community prone to stealing, as well as in the group of prisoners, but to a greater degree in the latter group. Finally, owing to the contradictory nature of the reported findings about the importance of the affective and interpersonal dimensions of psychopathy as a risk factor to predict criminal behavior, it is probably better to wait for more research to be done about this matter before taking a decision in favor or against these empirical findings (Colins, Andershed, & Pardini, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, several studies found that the interpersonal dimension of psychopathy had a better predictive utility for future criminal behavior than the affective dimension (Colins, Noom, & Vanderplasschen, 2012;Theobald et al, 2016;Vahl et al, 2014), and even in other studies, those dimensions did not add any predictive value to that of past personal criminal records (Colins, Andershed, & Pardini, 2015). Therefore, this study was performed in order to clarify to some extent these inconsistencies and contradictions in the evidence of the relationship between the components of psychopathy and the disposition to steal.…”
mentioning
confidence: 88%
“…Hillege, Das, and de Ruiter (2010) also reported that scores on the Dutch version of the YPI were related to self-reported adolescent substance abuse. Most recently, Colins, Andershed, and Pardini (2015) reported that the YPI was predictive of relational aggression, but not official or self-reported crime, using data from the Pittsburgh Youth Study. In terms of convergent validity, various research findings (e.g., Ansel, Barry, Gillen, & Herrington, 2014;Campbell, Doucette, & French, 2009) indicate that the YPI correlates with other measures of psychopathy, such as the Psychopathic Personality Inventory-Revised (PPI-R; Lilienfeld & Widows, 2005) and the Antisocial Process Screening Device (APSD; Frick & Hare, 2001).…”
mentioning
confidence: 99%
“…An affective dimension of psychopathy has been associated with externalizing behaviors in adults and in youths (Frick & White, 2008;Frick et al, 2014;Kahn et al, 2013;Kimonis et al, 2013;Kimonis et al, 2014;Lynam et al, 2011;Salekin et al, 2014). As noted by Colins et al (2015), the assessment of affective psychopathy may be relevant for risk assessment purposes and for intervention and treatment purposes. Existing psychopathy measures of adults and youth typically are designed to broadly encompass the interpersonal, affective, and behavioral/antisocial dimensions of psychopathy.…”
Section: Discussionmentioning
confidence: 99%